2021
DOI: 10.1113/ep088848
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive peripheral focused ultrasound neuromodulation of the celiac plexus ameliorates symptoms in a rat model of inflammatory bowel disease

Abstract: Individuals suffering from inflammatory bowel disease (IBD) experience significantly diminished quality of life. Here, we aim to stimulate the celiac plexus with noninvasive peripheral focused ultrasound (FUS) to modulate the enteric cholinergic antiinflammatory pathway. This approach may have clinical utility as an efficacious IBD treatment given the non-invasive and targeted nature of this therapy. We employed the dextran sodium sulfate (DSS) model of colitis, administering lower (5%) and higher (7%) doses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…This protective effect has been shown by activating CAP prophylactically or immediately following injury in multiple models of severe inflammation or trauma, including sepsis, haemorrhagic shock, postoperative ileus, and kidney ischemia reperfusion injury ( 1 , 6 , 19 , 21 , 40 , 45 , 46 ). The protective effect has also been shown in models of chronic and pathological inflammation, including collagen-induced and serum transfer models of arthritis and DSS-induced colitis ( 20 , 27 , 35 , 39 ). However, the activity of CAP, and the effect of stimulating the CAP pathway during progression of a local or acute infection has not previously been measured.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This protective effect has been shown by activating CAP prophylactically or immediately following injury in multiple models of severe inflammation or trauma, including sepsis, haemorrhagic shock, postoperative ileus, and kidney ischemia reperfusion injury ( 1 , 6 , 19 , 21 , 40 , 45 , 46 ). The protective effect has also been shown in models of chronic and pathological inflammation, including collagen-induced and serum transfer models of arthritis and DSS-induced colitis ( 20 , 27 , 35 , 39 ). However, the activity of CAP, and the effect of stimulating the CAP pathway during progression of a local or acute infection has not previously been measured.…”
Section: Discussionmentioning
confidence: 92%
“…These investigations have included models of endotoxemia ( 18 , 21 ), sepsis ( 21 ), hemorrhagic shock ( 45 ), postoperative ileus ( 46 ), and kidney ischemia reperfusion injury ( 40 ). This hypothesis has also been tested in models of inflammatory disease [such as collagen- or serum-induced arthritis ( 27 , 39 ) and chemical-induced colitis ( 35 )], in which the CAP pathway is activated to provide an anti-inflammatory effect in the presence of chronic inflammatory disease. In each of these models, electrical ( 2 ), ultrasonic ( 28 ), or pharmaceutical ( 32 ) activation of CAP resulted in reduced cytokine production and disease-alleviating therapeutic effects.…”
Section: Introductionmentioning
confidence: 99%
“…68 This pathway has recently been termed the ''enteric-CAP.'' 69 Thus, the vagus nerve once again appears key to the a7nAChR-mediated effects in IBD. Further research has suggested that the vagus nerve is capable of inducing a7nAChR-independent anti-colitic effects, such as by the recruitment of regulatory T cells (Tregs).…”
Section: Gastrointestinal Diseasementioning
confidence: 99%
“… 66 However, VNS, which has demonstrated efficacy in models of IBD, 67 has also been shown to reduce bowel inflammation independently of splenic innervation, and instead via cholinergic stimulation of α7nAChR-expressing resident macrophages in the gut. 68 This pathway has recently been termed the “enteric-CAP.” 69 Thus, the vagus nerve once again appears key to the α7nAChR-mediated effects in IBD. Further research has suggested that the vagus nerve is capable of inducing α7nAChR-independent anti-colitic effects, such as by the recruitment of regulatory T cells (Tregs).…”
Section: The Inflammatory Reflex In Diseasementioning
confidence: 99%
“…Modalities to enable more targeted and less invasive neuromodulation, including ultrasound, could expand the appeal of this approach, as proposed by GE Research and other groups. 188 , 193 , 194 …”
Section: Introductionmentioning
confidence: 99%